Yuni: Stereotype Representation Of Women - Mariesa Giswandhani (Politeknik Siber Cerdika Internasional, 2022)
This study was conducted to find out how the stereotypical representation of women is shown in the film titled Yuni. Yuni is a film produced by Fourcolours Films, Akanga Film Asia, Manny Film. There are criticisms that this film raises the stereotype of women in one of the areas in Indonesia which is the background for this film, namely Serang, Banten. This type of research is descriptive qualitative using the narrative analysis method of Vladimir Propp. The subject of this research is a film with the title Yuni which is seen from the narrative structure. Meanwhile, the object of research to be analyzed is the representation of women's stereotypes. The results showed that the film with the title Yuni was not able to optimally change the patriarchal pattern system. At first, the narrative of this film tries to break the stereotype of local culture with the strong stance of the main character named Yuni. However, the end of the film is very realistically depicted that women will tend to accept the existing stereotypes.